Ocena przydatności pomiaru kapitału intelektualnego w świetle badań ankietowych - Zielińska, Aleksandra (Value of Intellectual Capital - Questionnaire Survey, 2005)
There is no doubt that in the e-era the intellectual capital is the factor owing to which many companies in the modern world generate profits. In particular, this refers to the so-called companies based on knowledge, for instance consulting, informative or pharmaceutical companies. In the accounting system, the intellectual capital is understood as a difference between the market value and the book value of an enterprise. In accordance with this definition, it shall be treated as a balance item placed in the liabilities - close to financial capitals and its counterpart on the side of assets should be intangible assets. However, this is not what happens. Currently, the value of the intellectual capital is not shown anywhere. This means that there is no official document of financial reporting according to which it could be possible to define its value. This is not an advantageous situation either for the companies or for potential shareholders or investors. Primarily, because the picture of the company, its possibilities and profits is distorted. Furthermore, the lack of information related to intangible assets makes difficult their proper management and use. Precursors of the accounting for the intellectual capital have been trying to change this situation, introducing into the financial statements relevant documents which would present the status of the intellectual capital. This introducing must be preceded by measuring this type of capital in a correct way. A question is raised what Polish enterprises think about measuring of intellectual capital. Their views on this issue were sought by a questionnaire survey. The supreme purpose of this paper is to present the views of the companies subject to the questionnaire with reference to measuring the intellectual capital.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1079, s. 359-366